Konfirmatori faktor analisis kepuasan kerja dosen - Hazriyanto, H; Ibrahim, Badaruddin (Yayasan Melayu Berazam, 2018)
The University is one of the places to improve the quality of human resources. The development of education at the University of Batam city in particular has involved many parties, namely professors, the University, the community and other educational organizations. Job satisfaction in University lecturer becomes important to note. The lack of research on job satisfaction in University environment and the existing research is usually done in the industrial sector alone, so this study needs to be done at University. The object in this study to confirm the item indicators of job satisfaction lecturer. Data were collected using a questionnaire involves a number of 392 lecturers in Batam City University namely Putera Batam University, Batam University, and University of Riau Islands. Data were analyzed using SEM study of Amos. Results of the study found that, item 7 item confirming the satisfaction indicators indicators that can measure satisfaction with the Good of Fit is acceptable. The acquired results of the study can be used as a reference for the purposes of institutions, academics, and practitioners in making standards and evauasi job satisfaction. In addition, on behalf of the University needs to consider item indicators of satisfaction and need to also pay attention to other factors beyond the performed studies such as demographic factors, management and others.